Analisis Potensi Bencana Tanah Longsor di Kabupaten Banjarnegara Menggunakan Interpolasi Inverse Distance Weigthed (IDW) - Supit, Christanti Ekkelsia; Prasetyo, Sri Yulianto Joko (Building of Informatics, Technology and Science (BITS), 2024)
Landslides are a common disaster in Indonesia, especially in Banjarnegara Regency, caused by geomorphology and tropical climate. This is triggered by several factors, namely high rainfall and slope steepness, impacting communities and resulting in losses and even fatalities. According to data obtained from the BNPB website for the period of 2018-2023, there were 51 landslide disasters. Based on this background, the research problem formulates an analysis of landslide-prone areas using rainfall data, classification, and overlay techniques. The research objective is to produce mapping of areas potentially prone to landslides. The study discusses the analysis of rainfall data and slope classification, followed by overlay techniques to produce mapping. The research is supported by the Inverse Distance Weighted (IDW) method and overlay technique. The results obtained from the study include rainfall maps, slope maps, and landslide-prone maps from overlay results. Thus, based on the research findings, the conclusion is drawn that out of a total of 20 districts, there are 7 districts with a very high potential for experiencing landslides, namely Susukan, Mandarija, Madukara, Pagedongan, Sigalu, Pandanarum, and Pagetan